2021
DOI: 10.1177/19418744211009766
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Meningoencephalitis During Convalescence From Severe COVID-19 Pneumonia

Abstract: Invasive cryptococcal infection in a previously immunocompetent patient complicating coronavirus disease 2019 (COVID-19) pneumonia has not been described before. In this report, a 76-year-old woman survived a bout of respiratory failure from severe COVID-19 pneumonia, during which she received remdesivir, convalescent plasma, corticosteroids, and tocilizumab. Soon after discharge, she developed acute encephalopathy and multifocal ischemic strokes. CSF and blood cultures were positive for Cryptococcus neoforman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…Likewise, disseminated cryptococcosis [190], meningitis [191], invasive aspergillosis [192], CMV pneumonitis [193], and tuberculosis [194] were reported in patients who received tocilizumab (Table 2). In COVID-19 patients, different cases with cryptococcosis [24,65,[71][72][73], aspergillosis [88], strongyloidiasis [175], PCP [88], CMV [135], and HSV [143] infections were reported following tocilizumab use (Table 3). Inhibition of the JAKs pathway (ruxolitinib [195][196][197], baricitinib [198,199], and tofacitinib [200]), TNFα (infliximab [201,202]), IL-1 (Anakinra [203,204] and Canakinumab [205,206]), and GM-CSF (Mavrilimumab [207]) was also used for mitigating the CSS in COVID-19 patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, disseminated cryptococcosis [190], meningitis [191], invasive aspergillosis [192], CMV pneumonitis [193], and tuberculosis [194] were reported in patients who received tocilizumab (Table 2). In COVID-19 patients, different cases with cryptococcosis [24,65,[71][72][73], aspergillosis [88], strongyloidiasis [175], PCP [88], CMV [135], and HSV [143] infections were reported following tocilizumab use (Table 3). Inhibition of the JAKs pathway (ruxolitinib [195][196][197], baricitinib [198,199], and tofacitinib [200]), TNFα (infliximab [201,202]), IL-1 (Anakinra [203,204] and Canakinumab [205,206]), and GM-CSF (Mavrilimumab [207]) was also used for mitigating the CSS in COVID-19 patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that future studies are needed for standard diagnosis and new treatment options of these infections in COVID-19 patients (Table 4). [31,88] Candidiasis [43] Mucormycosis [60] Cryptococcosis [24,65,[71][72][73] Pneumocystis jiroveci (carinii) pneumonia [76,81,88,89] Histoplasma capsulatum [95,96,98] Coccidioides immitis [101,102] Strongyloidiasis [175,176] CMV [130,132,135,136] HSV [143] IL-6 blocker (Tocilizumab)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cases, studies and reviews specifically reported about meningoencephalitis in cases of COVID-19 [4] , [5] , [6] . The use of steroids and other immune modulatory therapies in the treatment of severe COVID-19 pneumonia predisposes these patients to the re-emergence of opportunistic infections [7] , [8] , [9] . Cytomegalo virus (CMV) reactivation is one of them [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%